IDEAL Problem Solving dalam Pembelajaran Matematika - Susiana, Eny (Kreano, Jurnal Matematika Kreatif-Inovatif, 2010)
Most educators agree that problem solving is among the most meaningful and importantkinds of learning and thingking. That is, the central focus of learning and instructionshould be learning to solve problems. There are several warrants supporting that claims.They are authenticity, relevance, problem solving engages deeper learning angtherefore enhances meaning making, and constructed to represent problems (problemsolving) is more meaningful. It is the reason why we must provide teaching and learningto make student’s problem solving skill in progress. There are many informationprocessingmodels of problem solving, such as simplified model of the problem-solvingprocess by Gicks, Polya’s problem solving process etc. One of them is IDEAL problemsolving. Each letter of IDEAL is stand for an aspect of thinking that is important forproblem solving. IDEAL is identify problem, Define Goal, Explore possible strategies,Anticipate outcme and Act, and Look back and learn. Using peer interaction andquestion prompt in small group in IDEAL problem solving teaching and Learning canimprove problem solving skill.Kata kunci: IDEAL Problem Solving, Interaksi Sebaya, Pertanyaan Penuntun, KelompokKecil.